Shortwave infrared spatial frequency domain imaging for detection of changes in tissue hydration - Livecchi, Thomas T.; Jacques, Steven L.; Pilvar, Anahita; Roblyer, Darren; Pierce, Mark C. (Frontiers in Photonics, 2025)
IntroductionWater and lipid content in biological tissues are important biomarkers for understanding physiological processes and diseases. Spatial frequency domain imaging (SFDI) provides a non-invasive method to quantify these components over a wide field of view. This study introduces an LED-based shortwave infrared (SWIR) SFDI system to measure tissue hydration.MethodsThe system was first validated using water-lipid dilutions of known concentrations. Subsequently, SWIR-SFDI was applied to ex vivo porcine skin undergoing desiccation to observe the relationship between reduced scattering and measured water content changes. Finally, the dorsal hand was imaged in three human subjects before and after exercise to assess changes in tissue induced by perspiration.ResultsFor the water-lipid dilutions, the system accurately predicted chromophore concentrations, validating the approach. In the skin desiccation experiments, small decreases in water content led to pronounced reductions in the reduced scattering coefficient, whereas absorption showed limited sensitivity. In vivo results showed a marked decrease in reduced scattering following exercise, consistent with a loss of tissue hydration.DiscussionThe findings suggest that, under the specific circumstances tested here, the reduced scattering coefficient may be a more sensitive indicator of tissue hydration than absorption. This sensitivity to small changes in water content underscores the potential clinical utility of SWIR SFDI for non-invasive hydration assessment in biological tissues. This technique offers promising applications for clinical diagnostics and physiological monitoring.